Optimizing talent class to increase student creativity - Hartanto, Dwi; Zuhaery, Muhammad; Santosa, Achadi Budi (Institute of Computer Science (IOCS), 2025)
This research explores the implementation of the talent class model at SMP Muhammadiyah Plus Gunungpring to foster student creativity. The talent class program, integrated into the school curriculum for the past four years, offers various classes in arts, sports, science and technology, languages, and life skills, catering to diverse student interests. The program involves all 7th and 8th-grade students, with classes held every Saturday for 2 hours. The selection process includes student class choices, assessments by instructors, and guidance from school counselors. The study utilizes a qualitative case study approach, employing in-depth interviews with teachers, students, and the principal, along with classroom observations and document analysis. Findings reveal that the talent class model implementation aligns with student-centered and project-based learning principles. Teachers act as facilitators, providing students the autonomy to explore and develop their talents, fostering a positive learning environment. Students actively participate in discussions, projects, and collaborative activities, demonstrating enthusiasm and a perception of increased creativity. The study identifies supporting factors such as school commitment, dedicated teachers, and student engagement, along with challenges like limited resources and parental involvement. The research concludes that the talent class model effectively fosters student creativity and provides recommendations for program enhancement.